Multiple recombinant events in human T-cell Leukemia virus Type 1: complete sequences of recombinant African strains - (:unkn) unknown (My University, 2020)
Africa is the largest endemic area for HTLV-1, with many molecular genotypes. We previously demonstrated that some strains from North Africa (a-NA clade) originated from a recombinant event between Senegalese and West African strains. A series of 52 new HTLV-1 strains from 13 North and West African countries were sequenced in the LTR region and/or a env gene fragment. Four samples from French Guyanese of African origin were also added. Furthermore, 7 complete sequences from different genotypes were characterized. Phylogenetic analyses showed that most of the new African strains belong to the Cosmopolitan a-genotype. Ten new strains from the a-NA clade were found in Morocco, Western Sahara, Mali, Guinea, Côte d'Ivoire and Ghana. A new a-G-Rec clade, which arose from a distinct recombination event between Senegalese and West African strains, was identified in Guinea and Ghana. The complete sequences suggest that recombination occur in the LTR as well as the env/pol region of the genome, thus a-NA and a-G-Rec strains have a mosaic profile with genetic segments from either a-WA or a-Sen strains. Our work demonstrates that recombination in HTLV-1 may not be as rare an event as previously proposed.
Keywords: African Research